Hubungan Antara Kontrol Diri dengan Perilaku Phubbing pada Mahasiswa - Khairunnisa Khairunnisa; Ade Nursanti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Phubbing is a behavior where someone uses their smartphone while interacting with others, engrossed in playing with their phone and avoiding direct communication. There are several factors that cause individuals to perform phubbing behavior. Some of these factors are smartphone addiction, Fear of Missing Out (FoMO), and low self-control. In today's era, smartphones contribute significantly to facilitating various activities in society. However, uncontrolled smartphone use can lead to various negative effects, one of which is phubbing behavior. This study was conducted to examine the correlation between self-control and phubbing behavior among college students. This research is non-experimental quantitative research with a correlational design. The sampling technique that used is accidental sampling with the number of samples obtained as many as 236 samples. The instruments used in this study are the Phubbing Scale (PS) and the Self Control Scale (SCS). Based on the results of this study showed that self-control has a significant and strong negative relationship with phubbing behavior among collage students.